The The Influence of Petrus Iohannis Olivi (1248-98) upon the Formulation of a Radically Voluntarist Conception of Natural Law - Whitehouse, Dominic (Pázmány Law Review, 2023)
The Franciscan thinker, Petrus Iohannis Olivi (ca. 1248–98), was the first latermediaeval thinker to propose a radically voluntarist theory of natural law. While his Franciscan predecessors, in particular Alexander of Halles (ca. 1185–1245), John of La Rochelle (end of 12th century–1245) and Saint Bonaventura(1221–1274) prioritised the higher will (voluntas) over the intellect in respect both to God himself as the providential giver of natural law, and of the human being as the recipient of God’s gift of natural law as an aspect of his eternal law, all these Franciscan thinkers regarded the operation of the intellect and will, first in the Divine and then in human nature in co-operative terms. Olivi is the first thinker to propose the absolute and not simply relative priority of the will in both the Divine creation of the natural law and how it impinges upon, and operates within the human rational faculty. In this brief introduction of Olivi’s theory, I focus on the first of these two perspectives.